Simulating a metallicity-dependent initial mass function: consequences for feedback and chemical abundances - Gutcke, Thales A.; Springel, Volker (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. Observational and theoretical arguments increasingly suggest that the initial mass function (IMF) of stars may depend systematically on environment,
Gesehen am 21.01.2019
Advance access publication 2018 October 8